2023
DOI: 10.3389/fcell.2023.1213995
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of alkaliptosis

Abstract: Malignant tumors represent a major threat to global health and the search for effective treatments is imperative. While various treatments exist, including surgery, radiotherapy, chemotherapy, immunotherapy and combination therapies, there remains a need to develop therapies that target regulated cell death pathways to eliminate cancer cells while preserving normal cells. Alkaliptosis, a pH-dependent cell death process triggered by the small molecular compound JTC801, has been identified as a novel approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Chen et al found that ATP6V0D1-mediated inhibition of the signal transducer and activator of transcription 3 (STAT3) increases alkaliptosis in pancreatic ductal adenocarcinoma cells and a high expression of ATP6V0D1 correlates with prolonged survival of patients with this carcinoma [ 41 ]. The induction of alkaliptosis, a type of regulated cell death driven by intracellular alkalization, plays an important role in tumor immunity and inflammatory response [ 42 ]. Meanwhile, it has been proved that caspase-8 (a well characterized initiator of apoptosis) can block the assembly of functional V-ATPase through binding to the V0 domain of V-ATPase, but not the V1domain, which leads to lysosomes alkalinization and, eventually, may induce LMP [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that ATP6V0D1-mediated inhibition of the signal transducer and activator of transcription 3 (STAT3) increases alkaliptosis in pancreatic ductal adenocarcinoma cells and a high expression of ATP6V0D1 correlates with prolonged survival of patients with this carcinoma [ 41 ]. The induction of alkaliptosis, a type of regulated cell death driven by intracellular alkalization, plays an important role in tumor immunity and inflammatory response [ 42 ]. Meanwhile, it has been proved that caspase-8 (a well characterized initiator of apoptosis) can block the assembly of functional V-ATPase through binding to the V0 domain of V-ATPase, but not the V1domain, which leads to lysosomes alkalinization and, eventually, may induce LMP [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…JTC801-induced alkaliptosis, partially via ATP6V0D1 targeting, offers a promising therapeutic avenue and an alternative strategy for tackling drug resistance. 73,74…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vivo experiments in mice showed that JTC801 selectively targets pancreatic ductal adenocarcinoma (PDAC) cells without harming normal cells. Two major signaling pathways, the ATPase H+ transporting V0 subunit D1 (ATP6V0D1)-signal transducer and activator of transcription 3 (STAT3) pathway and the NF-kB pathway, are reported to contribute to the induction of alkaliptosis (122,124,125). Blocking other cell death modes such as apoptosis, necroptosis, and ferroptosis did not prevent JTC801induced cell death.…”
Section: Alkaliptosismentioning
confidence: 99%